Earth Working Technologies, Driving The Land - Davronovna, Isayeva Kamola; Irgashovna, Khaidarova Iroda; Ikhtiyorovna, To’rayeva Dilafruz (European Journal of Life Safety and Stability (2660-9630), 2022)
To create favorable conditions for cultivated crops, mechanical impact on the soil with the working bodies of machines and weapons is called land (soil) cultivation. By tilling the soil, its water-physical properties, air, heat and nutrition regimes are improved, favorable conditions are created for the growth of plants. This article provides information about tillage technologies and tillage.